The Effect Of R&D Volatility on Market Value with The Role of Executive Overconfidence as a Moderating Variable - Dwi Indah Ratna Sari; Fitri Laela Wijayati (Accounting and Finance Studies, 2024)
This study aims to determine the effect of R&D Volatility on Market Value with the Role of Executive Overconfidence as a Moderating Variable. This study analyzes companies listed on the Indonesia Stock Exchange (IDX) in 2018-2021. The data used is secondary data from the company's annual financial statements. The population used in this study are companies listed on the Indonesia Stock Exchange (IDX) in 2018-2021. The sampling technique used was the purposive sampling technique. We obtained a final sample of 27 companies. The analysis technique used is panel data regression analysis using the Eviews 9 program. The results showed that the R&D Volatility variable positively affected market value. Overconfidence has a positive effect on market value. Executive overconfidence negatively moderates the relationship between R&D volatility and market value.